2014
DOI: 10.1080/02646838.2014.981801
|View full text |Cite
|
Sign up to set email alerts
|

Personal growth in UK and Croatian women following childbirth: A preliminary study

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. women respectively, reported a moderate level of growth after childbirth. Hierarchical multiple regression analyses showed that younger women in both countries reported more growth. In the UK sample approach coping strategies were related to higher growth. In the Croatian sample higher posttraumatic stress symptoms and the avoidant coping strategy of denial were associated with higher levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…However, positive psychological outcomes after childbirth have also been reported, such as psychological growth after traumatic events. For example, third of parturient women in Croatia and up to a half of parturient women in the UK experienced at least moderate growth after childbirth (Sawyer, Ayers, Young, Bradley, & Smith, 2012;Sawyer et al, 2015). Therefore, future studies should measure both negative and positive psychological outcomes after childbirth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, positive psychological outcomes after childbirth have also been reported, such as psychological growth after traumatic events. For example, third of parturient women in Croatia and up to a half of parturient women in the UK experienced at least moderate growth after childbirth (Sawyer, Ayers, Young, Bradley, & Smith, 2012;Sawyer et al, 2015). Therefore, future studies should measure both negative and positive psychological outcomes after childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examined predictors of PTSD symptoms prospectively and showed that higher levels of symptoms immediately after childbirth were significant predictors for higher levels of PTSD symptoms two months after childbirth (Srkalović Imširagić, Begić, Šimičević, & Bajić, 2017). Another recent study compared post-traumatic growth after childbirth in Croatian and UK women (Sawyer, Nakić Radoš, Ayers, & Burn, 2015) and showed that one in three women reported a moderate level of growth. Moreover, growth was predicted by coping strategies, where higher levels of growth were predicted by higher levels of problem-and emotion-focused coping in UK women but the higher levels of avoidance in Croatian women.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that women in our sample experienced posttraumatic growth (i.e., 'positive changes in beliefs or functioning as a result of challenging life events or circumstances'; (Tedeschi et al 1998), which may have positively impacted on the prenatal attachment relationship. Posttraumatic growth is higher in women who report higher levels of PTSD following childbirth (Sawyer et al 2012;Sawyer et al 2015) and includes a greater appreciation of life and relationships with others (Sawyer and Ayers 2009;Sawyer et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Slightly more research has looked at this postpartum. This evidence shows that a moderate amount of growth is reported by between 44% and 50% of women after birth (Sawyer & Ayers, 2009;Sawyer, Ayers, Young, Bradley, & Smith, 2012;Sawyer, Nakić Radoš, Ayers, & Burn, 2015). Common areas of growth are greater appreciation of life, personal strength, relating to others and new possibilities (Sawyer & Ayers, 2009;Sawyer et al, 2012).…”
mentioning
confidence: 99%
“…There is some indication that women who have more adverse experiences show more growth. This includes experiences such as operative birth (Sawyer et al, 2012), preterm birth (Noy, Taubman-Ben-Ari, & Kuint, 2015;Porat-Zyman, Taubman-Ben-Ari, & Spielman, 2017;Spielman & Taubman-Ben-Ari, 2009;Taubman-Ben-Ari, Findler, & Kuint, 2010) and women with symptoms of PTSD (Sawyer et al, 2012(Sawyer et al, , 2015. There is also indication that growth is associated with approach coping (Sawyer & Ayers, 2009;Sawyer et al, 2015) and more likely in younger women (Sawyer et al, 2015;Taubman-Ben-Ari et al, 2010).…”
mentioning
confidence: 99%